2018
DOI: 10.1159/000493466
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Treatment for Borderline Resectable Pancreatic Ductal Adenocarcinoma

Abstract: One of the main reasons for the dismal prognosis of pancreatic ductal adenocarcinoma (PDAC) is its late diagnosis. At the time of presentation, only approximately 15–20% of all patients with PDAC are considered resectable and around 30% are considered borderline resectable. A surgical approach, which is the only curative option, is limited in borderline resectable patients by local involvement of surrounding structures. In borderline resectable pancreatic cancer (BRPC), neoadjuvant treatment regimens have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
0
35
0
2
Order By: Relevance
“…Surgical treatment is the mainstay for curative treatment. However, only 15-20% of diagnosed patients have resectable disease, and only 30% have borderline resectable disease [1]. Radical surgery, including vascular reconstruction, has been reported as technically feasible, expanding surgical indications for PDAC [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment is the mainstay for curative treatment. However, only 15-20% of diagnosed patients have resectable disease, and only 30% have borderline resectable disease [1]. Radical surgery, including vascular reconstruction, has been reported as technically feasible, expanding surgical indications for PDAC [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the optimal NACT regimen has not yet been determined, a recent meta-analysis found that FOLFIRINOX-based NACT yielded better oncologic outcomes than gemcitabine-based NACT, despite the former having greater toxicity [1,7]. The resection rate after NACT was 65.3%, with 57.4% of the patients who underwent surgery achieving R0 resection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of PDAC often present with metastatic disease and consequently patient outlook is extremely poor [5]. Moreover, 15-20% of pancreatic cancer patients are deemed resectable whilst approximately 30% are borderline resectable [6]. Thus chemotherapy is the only available option to improve clinical outcomes for patients who have an unresectable disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic adenocarcinoma (PAC) is one of the most aggressive malignancies and causes in the United States approximately 53 000 deaths every year 1 . Despite considerable advances in surgical techniques and medical treatment, 2 the overall 5‐year patient survival of successful resections is an abysmal 20% 3 . Additionally, only 15% to 20% of patients present with surgically resectable disease.…”
Section: Introductionmentioning
confidence: 99%